2001
DOI: 10.1016/s0029-7844(01)01123-1
|View full text |Cite
|
Sign up to set email alerts
|

Provider attitudes about gaining consent for perinatal autopsy

Abstract: Physicians are not averse to seeking consent for perinatal autopsies. Midwives and nurses are influenced by the three factors studied, which might negatively influence the consent rate for perinatal autopsies. Intervention strategies aimed at changing nurses' attitudes should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 20 publications
3
23
1
Order By: Relevance
“…Although most likely to show concern over disfigurement, bereaved parents were singled out as the group especially likely to see benefits of a PM (listed in order of importance as advancement of medical knowledge, knowing the cause of death, and reassurance that all appropriate care was given). As 45% of those who did not permit a PM stated that they had not been approached, the authors argue, in contrast with the study by Khong and colleagues, 38 that reluctance of clinicians to offer PMs is likely to be more important than reluctance of relatives to sanction procedures.…”
Section: Parental Viewscontrasting
confidence: 56%
“…Although most likely to show concern over disfigurement, bereaved parents were singled out as the group especially likely to see benefits of a PM (listed in order of importance as advancement of medical knowledge, knowing the cause of death, and reassurance that all appropriate care was given). As 45% of those who did not permit a PM stated that they had not been approached, the authors argue, in contrast with the study by Khong and colleagues, 38 that reluctance of clinicians to offer PMs is likely to be more important than reluctance of relatives to sanction procedures.…”
Section: Parental Viewscontrasting
confidence: 56%
“…Directors of British neonatal units may have reservations about requesting an autopsy in some cases,2 but Australian neonatologists do not seem to share these 3. Nurses' attitudes may differ from doctors' 3. Grief counsellors, nurses, or social workers who may be in contact with parents can unconsciously send messages that discourage parents from consenting to an autopsy.…”
mentioning
confidence: 99%
“…A study found that while perinatal pathologist were the most knowledgeable about the autopsy procedure and its efficacy in determining the cause of death, they were less likely to meet the bereaved parents [126]. One Australian study showed that while midwives and neonatal nurses were reluctant to seek consent, obstetricians and neonatologists viewed nurses and midwives as influential on parent's decisions around autopsy [135]. Studies from USA, UK and Japan reported that nurses and midwives felt ill-equipped to deal with grieving parents and highlighted lack of experience, communication skills, confidence and competence to provide sensitive care [136].…”
Section: Investigation Of Stillbirthmentioning
confidence: 99%
“…Other factors that have been identified which affect clinicians' willingness to approach parents for autopsy consent include: low gestational age at death [135,139], the professional discipline of the clinician and their level of seniority [140], ambivalence about the value of autopsy [141], and lack of technical understanding of autopsy procedures [142]. Parents may regret their decision about autopsy as a result of poor communication or inadequate information [143].…”
Section: Investigation Of Stillbirthmentioning
confidence: 99%
See 1 more Smart Citation